What do you meme? the function of memes in tabloid newspapers - Tualla, Clarizzah Joi De Luna, 1998-
As meme culture rises online, tabloid newspaper have placed memetic content that are spread not only offline but also online as well. Memes have made tabloid newspapers more prone to the creation of "memefied" content or memes due to the reach it creates both offline and online, which translates to high readership and following. This study explores the 1,093 identified memes created in tabloid newspapers Bulgar, Balita, Bandera and Pilipino Star Ngayon from September 2017 to September 2018 through the integration of Barthes' Semiotic Theory (1957) and Gillian Rose's Compositional Interpretation (2016), and identities if these memes adhere to journalistic standard of accuracy and truthfulness. Textual and visual analysis of the semiotic codes, as well as analysis of the composition of memes were conducted to identify how memes are used in news and feature articles in tabloid newspapers. Focus interviews from the tabloid newspapers editor were conducted to assess the creation, placement and significance of these memes in the newspaper. The study establishes that memes are created to gather and attract readers and a following through their satirical and humorous content, and to accompany and visualize an article in tabloid newspapers. However, the study also concludes that solely the memes used to accompany and visualize an article do not adhere to journalistic standards. The focus interviews prove that these memes are created in awareness of each other, that they are created to attract readers and accompany an article, and that some of these memes do not adhere to journalistic standards.